Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning di Kelas IV Sekolah Dasar - Zekri, Nira Elviana; Lena, Mai Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
The purpose of this study was to improve thematic integrated learning process using Discovery Learning model at grade 4 of SD Kartika 1-11 Padang City. This research was classroom action research, consisted of 2 cycles each cycle consisted of planning, action, observation and reflection.  Subjects of this research were teachers and 21 grade 4 students in SD kartika 1-11 padang City. Data of this research were obtained from the assessment of lesson plans, and learning processes. Techniques of data collection were document analysis, and observation. Instruments of this research were lesson plan assessment sheet and observation sheet. The results of the study showed that there were an increase in: a) the assessment of lesson plan in cycle I was 84,37% (good) and went up to 93.75% (very good) in cycle II; b) the result of observation of teacher aspect in cycle I was 81.25% (good) and increased to  90,.62% (very good) in cycle II; c) the result of observation of student aspect in cycle I was 81.25% (good) and increased to  90.62% (very good). It can be concluded that the Discovery Learning model can improve thematic integrated learning process in elementary schools.